1992
DOI: 10.1093/ajh/5.3.111
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Blood Pressure Variation and Cardiac Mass in American Blacks and Whites and South African Blacks

Abstract: American blacks exhibit higher nocturnal blood pressure than American whites with similar daytime pressure. To determine whether this represents a true racial difference, as opposed to a consequence of different environmental factors, we measured ambulatory blood pressure, cardiac left ventricular mass, and urinary electrolyte excretion in 22 South African blacks (15 women, aged 36 +/- 12 years) and age, sex, and daytime mean pressure-matched American blacks and whites. While all three groups exhibited similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 0 publications
1
36
1
Order By: Relevance
“…The increased cardiovascular load may contribute to the much higher prevalence of cardiovascular morbidity and mortality in AAs compared with EAs. Although the basis for the differential nocturnal decline between AAs and EAs is not currently known, the fact that blacks outside of the United States experience the same nocturnal decline as whites 32 and that FH of EH can only account in part for the ethnic difference seen here and elsewhere suggest that the ethnic difference in ABP patterns is the result of a gene-environment interaction. We have hypothesized that pressure remains elevated at night in an attempt to excrete the daily sodium load.…”
Section: Discussionmentioning
confidence: 78%
“…The increased cardiovascular load may contribute to the much higher prevalence of cardiovascular morbidity and mortality in AAs compared with EAs. Although the basis for the differential nocturnal decline between AAs and EAs is not currently known, the fact that blacks outside of the United States experience the same nocturnal decline as whites 32 and that FH of EH can only account in part for the ethnic difference seen here and elsewhere suggest that the ethnic difference in ABP patterns is the result of a gene-environment interaction. We have hypothesized that pressure remains elevated at night in an attempt to excrete the daily sodium load.…”
Section: Discussionmentioning
confidence: 78%
“…In the current study black hypertensives had higher awake and sleeping diastolic blood pressures and less of a nocturnal drop in systolic blood pressure than did white hypertensives. Although higher night-time mean blood pressures in normotensive AfricanAmericans [39] and Afro-Caribbeans [31] in comparison with those in white normotensives have been reported, the magnitude of the nocturnal fall did not differ between the races [31]. Despite black nondippers having significantly greater sleeping blood pressures than do black dippers (140/86 versus 129/80 mmHg, P < 0.005 systolic and P < 0.05 diastolic), we detected no differences between the two groups in cardiac and vascular structure.…”
Section: Discussionmentioning
confidence: 89%
“…In other studies, African Americans have been shown to have higher nighttime BP than whites despite similar daytime BP. 23,24 The majority of patients with uncomplicated hypertension experience a fall in their nighttime BP of Ͼ10% of the daytime mean arterial BP. The absence of a fall in nocturnal BP has been linked to target organ damage, such as carotid artery structural alterations and LVH in some studies [25][26][27][28][29] but not others.…”
Section: Discussionmentioning
confidence: 99%